A Component-Based Coordinate System for Static and Dynamic Evaluation of Standard Transtibial Prosthesis Alignment. Issue 4 (October 2020) - Zabala, Michael E.; Gupta, Raju; Dueitt, Madeline; Pasquerello, Nicholas; Vazquez, Adan
ABSTRACT: Introduction: Lower-limb loss is a disability that is currently estimated to affect more than one million Americans. Provision of a prosthetic lower limb oftentimes restores the ability of the individual to reengage in society by returning to work, sports, military service, or other activities requiring mobility. However, it is critical that these devices are properly aligned to avoid or reduce discomfort, pain, and even serious bone disorders such as osteoarthritis, osteopenia, and osteoporosis. Much work has been done on static prosthesis alignment measurement, and devices and tools currently exist to aid the prosthetist in this task. However, to the authors' knowledge, there is currently no standardized coordinate system for objectively calculating and expressing prosthesis alignment that can be used during both static and dynamic activities. Methods: The techniques presented here provide a method of creating component-specific coordinate systems for a standard transtibial prosthesis for the purpose of calculating objective measures of alignment while the prosthesis is being worn during both static and dynamic activities. This method is based upon a selection of anatomically relevant points tracked on the residual limb and the prosthesis, along with Euler angle decomposition techniques. A case study analysis was performed on one transtibial test subject to demonstrate the methods presented. Results: A method for tracking both static and dynamic transtibial prosthesis alignment was established. This method may be used with modern motion-tracking technology that was not widely available when previous static alignment methods were established. Conclusions: The potential benefit of this standardized method is improved understanding of the relationship between objective measures of prosthesis alignment and various measures of patient outcomes and success such as pain, discomfort, and daily steps walked. A standardized means of calculating and expressing prosthesis alignment will also benefit the design and development of future alignment tool technology. Abstract : Supplemental digital content is available in the text.